Do doctors have a duty to treat during a pandemic? (UCC Student Medical Journal, 2024)
Medicine is a humanitarian profession and as stated in the Oath, doctors have a duty to help the sick. However, is this duty absolute? Can physicians refuse to treat patients? Even when there is significant risk to their own health? How about their duty as a spouse, parent or family member? These questions emerge during a health emergency and have been debated during the current COVID-19 pandemic.
Keywords: Ethical Discussion; pandemic; duty to treat